Optimization of masonry units for single leaf walls using a Genetic Algorithm - Luísa C. Sousa (2012)
Nowadays new masonry solutions are growing, due to thermal efficiency requirements including the new European Directivesregulations. To answer these new challenges two ways are mainly available, to add higher thickness of thermal insulation inassociation with current masonry units walls, or to change masonry units, combining improved thermal insulation with enoughmechanical resistance. This paper describes the recent development of a new masonry system, based on lightweight concrete units,intended for construction of large single leaf external walls without thermal insulation materials. A detailed analysis and optimizationusing the finite element method have been performed, under thermal behaviour. A developed computational method searches a newtopology for lightweight concrete blocks that will perform according to todays normative requests exhibiting optimal thermalinsulation behaviour. The optimisation problem considers an objective function that measures the masonry wall thermal performancecalculated through three-dimensional finite element computer simulations. A genetic algorithm is proposed in order to obtain theoptimal solution. An illustrative example of vertically perforated blocks is presented demonstrating the applicability and efficiency ofthe optimization method. Concerns with mechanical behaviour, productivity and ergonomic are also considered according to theirimportance in the final cost.